Food-Web Structure in Four Locations Along the European Shelf Indicates Spatial Differences in Ecosystem Functioning - Silberberger, Marc J.; Renaud, Paul E.; Kröncke, Ingrid; Reiss, Henning (Frontiers in Marine Science, 2018)
Studies of trophic interactions give valuable insights into the functioning of ecosystems and can be used to identify qualitative differences among ecosystems. Here, we use natural stable isotope concentrations (δ13C and δ15N) to study the food-web structure in four contrasting locations on the northern European continental shelf: two sub-Arctic locations in the Lofoten-Vesterålen region (fjord vs. open shelf) and two temperate locations (northern vs. southern North Sea). Phytoplankton was identified as the major primary producer in all studied ecosystems, even in the sub-Arctic fjord, where macroalgae only played a minor role in the food web. We used mixing models to determine the relative reliance on prey of benthic affinity and found that reliance on benthic prey was higher in the North Sea than in the Lofoten-Vesterålen region. Atlantic cod (Gadus morhua) was identified as the single top-predator in the North Sea, utilizing food from both, benthic and pelagic trophic channels. More separate benthic and pelagic trophic channels characterize the Lofoten-Vesterålen region, where G. morhua acts as part of the pelagic food chain. Furthermore, our data indicate that the recent mesopredator outburst in the southern North Sea might have been enhanced by reduced predation pressure due to the collapse of the local cod stocks. We conclude that the resilience towards a high fishing pressure is higher in the Lofoten-Vesterålen region than in the North Sea.